2005
DOI: 10.1248/jhs.51.514
|View full text |Cite
|
Sign up to set email alerts
|

Study of 1,4-Dioxane Intake in the Total Diet

Abstract: 1,4-Dioxane is a newly added compound to the water quality standards in Japan that were revised in 2003. In order to estimate the contribution of 1,4-dioxane in drinking water to the total exposure in humans, it is necessary to take into account the quantity of the compound in food. In an earlier study, we measured the intake of 1,4-dioxane in food based on the average consumption of food in the Kanto area.1) The total daily intake of 1,4-dioxane was calculated to be 0.440 g. In the present study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…FDA [ 840 ] estimated per capita dietary intake of 1,4-dioxane to be low, averaging at 0.6 µg/person/day. Analyses of Japanese foods revealed an EDI of 1,4-dioxane averaging from 0.44 to 4.5 µg/kg bw/day [ 818 , 841 ]. SCF established that an estimated maximum exposure to 1,4-dioxane as a constituent of food additives, polysorbates, in bread ranges between 0.008 to 0.05 µg/kg bw/day [ 817 ].…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…FDA [ 840 ] estimated per capita dietary intake of 1,4-dioxane to be low, averaging at 0.6 µg/person/day. Analyses of Japanese foods revealed an EDI of 1,4-dioxane averaging from 0.44 to 4.5 µg/kg bw/day [ 818 , 841 ]. SCF established that an estimated maximum exposure to 1,4-dioxane as a constituent of food additives, polysorbates, in bread ranges between 0.008 to 0.05 µg/kg bw/day [ 817 ].…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…C 4 H 8 O 2 is not biodegradable and was classified as a potential carcinogen by the US Environmental Protection Agency (EPA). Widely used as an industrial solvent, C 4 H 8 O 2 is considered as the major anthropogenic source of 1,4-dioxane in the atmosphere [ 89 , 90 ]. Chandran et al [ 65 ] reported a novel FT-IBBCEAS to record the absorption of C 4 H 8 O 2 in the spectral range of 5900−8230 cm −1 with a resolution of 0.08 cm −1 .…”
Section: Target Gas Species Performances In Laboratorymentioning
confidence: 99%